Kinerja Sosial Perbankan Syariah Di Indonesia: Peran Intellectual Capital, Sharia Compliance, Dan Dewan Pengawas Syariah - Felia Oktafiani; Bima Cinintya Pratama; Azmi Fitriati; Tiara Pandansari (Universitas Muhammadiyah Malang, 2022)
Islamic banking in carrying out its performance is not only business-oriented but also social orientation while still based on Islamic principles, that is what distinguishes Islamic banks from conventional banks. Social performance in Islamic banks can be realized through its role in providing benefit to mankind based on Sharia goals. The purpose of this study was to determine the effect of Intellectual Capital, Sharia Compliance, Education, and Reputation of the Sharia Supervisory Board on Social Performance. The population used in this study is Islamic Commercial Banks in 2008-2020 which are registered with the Financial Services Authority. The sampling technique used is purposive sampling technique with pooled unbalance sample in order to obtain observational data of 131 data that have met the criteria. The data analysis technique used is multiple regression analysis. The results of this study indicate that the variables of Sharia Compliance, Education, and Reputation of the Sharia Supervisory Board (SSB) have a significant positive effect on the Social Performance of Islamic banking. While the variable Intellectual Capital does not affect the social performance of Islamic banking. If Islamic banking in Indonesia is able to maximize the implementation of sharia compliance, maintain the quality of DPS education, as well as the reputation of DPS to remain good, the social performance will be even better, this can also be supported by intellectual capital if its implementation is managed and maximized.